Book Review: Growing the next generation of researchers: A handbook for emerging researchers and their mentors. Holness, L. - Motshoane, Puleng; Muthama, Evelyn; McKenna, Sioux (Critical Studies in Teaching and Learning, 2023)
Review of:Â Holness, L. 2015. Growing the next generation of researchers: A handbook for emerging researchers and their mentors.Â ISBN 978-1-77582-085-7. Pbk. Xxii + 258pp.